Peningkatan Kapasitas Tata Kelola Desa Wisata Berbasis Masyarakat dan Berkelanjutan - Palupi, Santi; Bahri, Asep Syaiful; Ayuningsih, Sri Fajar; Abdillah, Fitri; Rahmat, Timotius Agus (Dharma: Jurnal Pengabdian Masyarakat, 2024)
Cilember Tourism Village is a tourist destination in the administrative area of Cilember Village, Cisarua District, Bogor Regency. Cilember Tourism Village was initiated in early 2015 by the Cilember Village community tourism awareness group. In its development, Cilember Tourism Village still experiences various obstacles in realizing a sustainable tourism village, including related to the lack of understanding of tourism village managers regarding village governance. This community service is carried out with the aim of providing an understanding of tourism village governance. The target of this community service is the manager of the Cilember Tourism Village. The method of implementing community service used is by using lectures, discussions and practices. The results of community service were obtained, that the participants of the activity easily understood the training material provided. Participants in the activity also gave assessments to community service implementers who were able to accommodate questions and discussions carried out. The suggestion from this activity is the need for additional time for activities and imitation study activities to villages that have developed and implemented good governance. The suggestion for the next training activity is to increase the capacity of homestay governance in tourist villages.